1976
DOI: 10.1093/jn/106.5.653
|View full text |Cite
|
Sign up to set email alerts
|

Stability of some Pyridoxal Phosphate-dependent Enzymes in Vitamin B-6 Deficient Rats

Abstract: The effects of lowering the liver pyridoxal phosphate (PLP) concentration by vitamin B-6 deficiency on the stability of several rat liver enzymes were examined. Three PLP-dependent enzymes (serine dehydratase, ornithine-delta-aminotransferase, and tyrosine aminotransferase) and two non-PLP-dependent enzymes (glucose-6-phosphate dehydrogenase and phosphoenolpyruvate carboxykinase) were induced in vitamin B-6 deficient and control rats by feeding them high-protein diets or by injecting them with glucagon or dexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In fact, it has been proposed that the extent to which a B6dependent enzyme is inhibited by an antimetabolite is a function of the relative affinities of the apoenzymes toward the coenzyme (Snell, 1958) and that, therefore, in an in vivo experiment, antimetabolites do not necessarily inhibit all B,-dependent enzymes to the same degree, but particularly those whose coenzyme will easily dissociate from the apoenzyme (Holtz and Palm, 1964). To interpret this in different terms, the differences in the proportions of enzymes existing as holo-and apoenzyme determine the extent of inhibition (Hunter and Harper, 1976). These findings of B, enzymes catalyzing different reactions obviously also hold for the same enzyme with regionally different properties.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been proposed that the extent to which a B6dependent enzyme is inhibited by an antimetabolite is a function of the relative affinities of the apoenzymes toward the coenzyme (Snell, 1958) and that, therefore, in an in vivo experiment, antimetabolites do not necessarily inhibit all B,-dependent enzymes to the same degree, but particularly those whose coenzyme will easily dissociate from the apoenzyme (Holtz and Palm, 1964). To interpret this in different terms, the differences in the proportions of enzymes existing as holo-and apoenzyme determine the extent of inhibition (Hunter and Harper, 1976). These findings of B, enzymes catalyzing different reactions obviously also hold for the same enzyme with regionally different properties.…”
Section: Discussionmentioning
confidence: 99%
“…Because chronic ethanol consumption reduces plasma and tissue concentrations of PLP (46), a factor necessary for ODC activity (47), it is tempting to speculate that posttranslational inhibition of ODC activity is due to PLP deficiency. However, while PLP deficiency may contribute to ethanol-associated inhibition of polyamine synthesis in vivo, it cannot explain the inhibition of ODC activity noted in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together these findings suggest that PLP may stabilise mutant CS molecules possibly by influencing the proportions of apo-and holo-CS in vivo, in a similar manner to that observed for other PLP enzymes. For example, tyrosine aminotransferase (EC 2.6.1.5) in the liver of rats (Snape et al, 1980), serine dehydratase (EC 4.2.1.13) in vitamin B6-deficient rats (Hunter and Harper, 1976), aspartate aminotransferase (EC 2.6.1.1) in rat tissues (Okada and Hirose, 1979) and, finally, partially purified cystathionase which was protected by PLP against degradation by proteolytic enzymes (Chatagner et al, 1970). Recently, Skovby et al (1984) have reported studies of biogenesis ofCS subunits which suggest that there can be a normal rate of synthesis of mutant CS molecules whose stability is much reduced.…”
Section: Interaction Of Mutant Cs With Plpmentioning
confidence: 99%